2022
DOI: 10.3389/fendo.2022.812032
|View full text |Cite
|
Sign up to set email alerts
|

MOTS-c and Exercise Restore Cardiac Function by Activating of NRG1-ErbB Signaling in Diabetic Rats

Abstract: Pathologic cardiac remodeling and dysfunction are the most common complications of type 2 diabetes. Physical exercise is important in inhibiting myocardial pathologic remodeling and restoring cardiac function in diabetes. The mitochondrial-derived peptide MOTS-c has exercise-like effects by improving insulin resistance, combatting hyperglycemia, and reducing lipid accumulation. We investigated the effects and transcriptomic profiling of MOTS-c and aerobic exercise on cardiac properties in a rat model of type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
2
12
2
Order By: Relevance
“…Li et al, MOTS-c therapy and regular aerobic exercise for 8 weeks altered 98 and 47 pathogenic genes, respectively, with 24 genes related to angiogenesis, inflammation, and apoptosis overlapping. These data imply that both MOTS-c and exercise reduce diabetic heart dysfunction through similar pathways [ 113 ].…”
Section: What Are Mitochondrial Derived Peptides (Mdps)?mentioning
confidence: 99%
“…Li et al, MOTS-c therapy and regular aerobic exercise for 8 weeks altered 98 and 47 pathogenic genes, respectively, with 24 genes related to angiogenesis, inflammation, and apoptosis overlapping. These data imply that both MOTS-c and exercise reduce diabetic heart dysfunction through similar pathways [ 113 ].…”
Section: What Are Mitochondrial Derived Peptides (Mdps)?mentioning
confidence: 99%
“…Furthermore, human studies showed that exercise increased MOTS-c levels in skeletal muscle and blood circulation, indicating that MOTS-c is a mitochondrial-derived peptide induced by skeletal muscle exercise ( 9 , 10 ). Additionally, more and more studies have revealed the importance of MOTS-c in regulating obesity and diabetes ( 11 , 12 ), longevity ( 13 ), and cardiovascular disease ( 14 ). Specifically, this paper discusses the application of mitochondrial-derived peptides, including MOTS-c, in the treatment of diseases and anticipates the future development direction of MOTS-c combining synthetic biology to provide new ideas on how it can be developed and applied.…”
Section: Introductionmentioning
confidence: 99%
“…Rats in group C were placed on the non-moving treadmill (i. e., no exercise) for 60 minutes. Compressed air and tactile stimuli were used to prompt continuous running of rats during exercise 25 .…”
Section: Methodsmentioning
confidence: 99%